A critical review on petrogenetic, metallogenic and geodynamic implications of granitic rocks exposed in north and east China: New insights from apatite geochemistry - Zafar, Tehseen; Rehman, Hafiz Ur; Mahar, Munazzam Ali; Alam, Masroor; Oyebamiji, Abiola; Rehman, Saif Ur; Leng, Cheng-Biao (Journal of geodynamics, 2020)
[Display omitted] •Magmatic apatite reflects the parental magma attributes of Luming and Lower Yangtze granites.•Apatite Sr contents and REEs ratios serve as significant proxies to trace the differentiation history of granitic rocks.•Apatite chemical constituents act as a vigorous tool to identify mineralization and regional metallogeny of plutons.•Apatite chemistry is a valuable and powerful proxy to evaluate the tectonic evolution of granites. Apatite is significant phosphate-bearing accessory mineral that is omnipresent in most granitic rocks. In this study, we present geochemical characteristics of magmatic apatites from the Luming and Lower Yangtze granitic belts of NE and eastern China to explore their potential in petrogenesis, mineralization and tectonic evolution of granites. The petrogenetic, metallogenic and tectonic aspects of these granites remain subjects of great debate. This review aims to clarify these issues based on apatite geochemistry. The investigated apatites from both these localities are mainly fluorapatites reflecting the actual attributes of parental melts. Apatites from Luming and Lower Yangtze River Belt (LYRB) exhibit strong negative Eu anomalies suggesting plagioclase crystallization earlier than apatite. The negative correlation of Eu/Eu* (δEu) vs Mn, δEu vs δCe and δEu vs Ga in the apatites signifies that the parental magmas of both granites are produced under moderate reduced conditions. The Sr contents and REEs ratios in apatites serve as significant proxies to trace the differentiation history of Luming and Lower Yangtze granitic plutons. The apatites Sr/Y ratios vs δEu also exhibit that both granites are non-adakitic in nature which is consistent with the host rocks non-adakitic affinities. Halogen data indicates that apatites of Lower Yangtze comprising more chlorine (0.02–1.45 wt.%) and less fluorine (1.51–3.85 wt.%) are linked with slab dehydration whereas apatites from Luming having lower Cl (0–0.04 wt.%) and higher F contents (3.36–5.29 wt.%) suggest association of granites with partial melting of juvenile crust material. Based on the positive correlation of SO3 with Li, (La/Sm)N vs (Yb/Sm)N and obvious variations of (La/Yb)N vs Eu/Eu*, it is inferred that these host rocks are ore-associated. Furthermore, geochemical signatures of apatites from LYRB show low F/Cl ratios, stable La/Sm ratios, high δEu (0.04–0.43, average 0.21) and low δCe values (0.96–1.12, average 1.02) indicating that the magmas of these granites have association with slab dehydration and linked with Cu–Mo–W mineralization, induced from the mutual impacts of Paleo-Pacific plate subduction and intraplate extension. In comparison, fairly high F/Cl ratios, La/Sm ratios, low δEu (0.12–0.23, average 0.16), high δCe values (0.98–1.09, average 1.04) and low Sr/Th ratios of Luming apatites infer that the Mo–W bearing granites are originated in consequence of partial melting of juvenile crustal material. Based on apatite geochemistry, we document first time varieties of ore deposits specifically Mo–W and Cu deposit in LYRB and Mo–W deposit in Luming which are developed under lower oxygen fugacity. The compiled geochemical data and interpretations propose that apatite chemical constituents are worthwhile to pinpoint polymetallic mineralization and fingerprint for ore types. In view of these findings, we confirm that apatite is not only consistent to trace geological facts about parental magma characteristics but also a reliable pointer of geodynamic evolution and ore varieties.